1987
DOI: 10.1111/j.1469-7610.1987.tb00679.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Depression in Young Children

Abstract: An urban working class sample of depressed mothers with two-yr-old children was compared with a control group of non-depressed mothers using maternal interviews, home observation of mother/child interaction, and developmental assessment of the children. Measures were repeated after six months. Children of depressed mothers showed more emotional and behavioural disturbance and delay in expressive language development. Depressed mothers had more past and current adverse experiences, particularly in close relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
213
0
14

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(234 citation statements)
references
References 4 publications
(4 reference statements)
7
213
0
14
Order By: Relevance
“…Parents who are going through a separation and are also experiencing mental health issues may not be able to parent as well, and have as good a parent-child relationship, as those who are not affected by mental health issues. This direction of the relationship has also been found in previous research (Cox, Puckering & Pound, 1987;Taylor & Andrews, 2009). …”
Section: The Relationship Between Mental Health and Parenting Variablessupporting
confidence: 71%
See 1 more Smart Citation
“…Parents who are going through a separation and are also experiencing mental health issues may not be able to parent as well, and have as good a parent-child relationship, as those who are not affected by mental health issues. This direction of the relationship has also been found in previous research (Cox, Puckering & Pound, 1987;Taylor & Andrews, 2009). …”
Section: The Relationship Between Mental Health and Parenting Variablessupporting
confidence: 71%
“…A study by Cox, Puckering and Pound (1987) showed that depressed mothers were less likely to respond to their child"s signals toward them, were less likely to engage their child in social interactions, and had more difficulty responding to their child"s cues than nondepressed mothers. Furthermore, Kuczynski (1984) found that depressed parents were more likely to choose discipline strategies that required less cognitive effort and tended to become overly permissive or authoritarian rather than taking the time and effort to negotiate or talk things through.…”
Section: Extant Literature -Mental Health and Parenting Variablesmentioning
confidence: 99%
“…The speech of non-depressed mothers is characterised by short utterances, repetition, high rates of imperatives and interrogatives, few directives and controlling statements or corrections, and is focused on the children's experience (Murray & Trevarthen, 1986;Snow, 1977). In contrast, speech of depressed mothers is focused on the mother's own experience, contains a high percentage of negative affect, spare use of explanations, suggestions and questions, as well relatively few acknowledgements of infant agency (Cox, Puckering, Pound & Mills, 1987;Murray, et al, 1993). Several studies have shown that children of depressed mothers in comparison with children of non-depressed mothers have more difficulties in expressive language, perform poorly on measures of cognitive-linguistic functioning and are less co-operative at 36 months (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Infants aged as young as 3 months have been shown to ably detect their mother's mood and to modify their own responses accordingly (10). While cognitive skills (11), expressive language development (12), and attention (13) have been negatively influenced by PPD, it has also been reported that children of mothers with depression are 2 to 5 times more likely to develop long-term behavioural problems (14,15). Child neglect and (or) abuse (16) and marital stress resulting in separation or divorce (17,18) are other reported outcomes.…”
mentioning
confidence: 99%